An historical demographic investigation into mortality in three historical birth cohorts born between 1837 and 1900 in Mamre, with special reference to life expectancy - Katzenellenbogen, Judy Masha (Department of Public Health and Family Medicine, 2018)
This thesis reports on an historical prospective study of three Mamre decadal birth cohorts (1837-1846, 1870-1879, and 1900-1909) constructed retrospectively through existing parish records of the Moravian Mission at Mamre in the Western Cape region of South Africa. Nominative data collection techniques were used to gather information needed to determine the infant mortality rates, quinquennial mortality rates and life expectancies of the three cohorts. Issues related to the quality of data – non-registration and follow-up - were investigated. Birth registration was best for the 1837-46 cohort for males and females, with the 1900-1909 registration being next best. Overall, male registration coverage was substantially better than that for females. Infant death registration was best for males in these 2 cohorts, but were poor for females. Based on these data, the infant mortality rates for the cohorts born in 1837-1846, 1870-1879 and 1900-1909 - 196, 182 and 128 per 1000 respectively for males and 160, 172 and 97 per 1000 respectively for females - appeared to be underestimates. There is some evidence of a downward trend for the infant mortality rates with time for males, but this was not statistically significant. Quinquennial mortality rates for the 3 cohorts did not differ statistically, and are similar to the 1935-37 national 'coloured' figures. The life expectancies also did not differ significantly between cohorts. The life expectancies at birth (range 34- 40 years for males and 32-45 years for females) were probably overestimates due to biased IMR's. The life expectancies at age 1 (range 41-44 for males and 37-49 for females) were more representative figures. Life expectancies at age 20 were fairly stable over time (37-45 years) except for females in the 1900-1909 cohort whose life expectancies were substantially higher than earlier figures. All mortality indices investigated in this study consistently showed a lighter burden of mortality in historical Mamre compared to 'coloureds' in the Cape Colony at the turn of the century. This is probably associated with the better housing, environmental, social, economic and educational conditions at the Mamre mission relative to the rest of the Colony in the century after the emancipation of slaves.